The Art of Predicting Project Failure: A Review of the Breaking Point Evolution Model and its Implications for Project Management - Ali Fadhil Jawad; Mostafa Ghazimoradi; Majid Safehian (Migration Letters, 2023)
This review article aims to provide an in-depth analysis of the Breaking Point Evaluation Model and its effectiveness in predicting project failure. We conducted a systematic review of the literature, including both Persian and English articles, to explore the evolution, criticisms, and future directions of the model. We found a total of 15 articles that met our inclusion criteria, including 5 Persian and 10 English articles. The majority of the articles focused on the application of the Breaking Point Model in project status assessment and its strengths and limitations. However, some articles also explored alternative models for evaluating project progress and failure. Our analysis revealed that the Breaking Point Model is a useful tool for predicting project failure, as it provides a clear framework for identifying critical points in a project’s lifecycle where failure is likely to occur. However, the model has some limitations, including its reliance on subjective assessments and the difficulty of accurately predicting future events. Despite these limitations, the Breaking Point Model remains a valuable tool for project management, particularly when used in conjunction with other assessment tools. Future research should focus on refining the model to address its limitations and exploring new approaches to project evaluation. In conclusion, this review article provides a comprehensive analysis of the Breaking Point Evaluation Model and its implications for project management. While the model has some limitations, it remains a valuable tool for predicting project failure and identifying critical points in a project’s lifecycle. We recommend that project managers consider using the Breaking Point Model in conjunction with other assessment tools to improve their ability to predict project outcomes.